GIS APPLICATION TO COMPREHENSIVE PREDICTION OF ENVIRONMENTAL IMPACTS OF AIR POLLUTION IN COASTAL INDUSTRIAL AREAS: CASESTUDY OF MINH DUC - BEN RUNG INDUSTRIAL AREA, THUY NGUYEN DISTRICT, HAI PHONG CITY - Lan, Tran Dinh; Ve, Nguyen Dac (Vietnam Journal of Marine Science and Technology, 2009)
GIS technology was applied to assessment and comprehensive prediction of environmental impacts of air pollution in Minh Duc- Ben Rung as an example for the potentials of this technology in study on environmental assessment and prediction, particularly on environment impact assessment and strategic environment assessment. Information layers of the study area on air quality (resulted from ISC3 conputer model), landcover/landuse and socio-economic infrastructure stored in GIS database were overlayed to make assessment and comprehensive prediction of the environment and local community health. Study outcomes show the risks of air pollution and local community health due to air pollution were high in Minh Duc County then followed by Tam Hung – Lap Le communes of Hai Phong City.